1984
DOI: 10.1177/00220345840630091301
|View full text |Cite
|
Sign up to set email alerts
|

Dental Disease and Work Loss

Abstract: Few studies have analyzed dental diseases in terms of their social impact. This study explored the feasibility of a social outcome measure, work absence. 2600 employed people in the Hartford (CT) area were interviewed by 'phone using Random Digit Dialing methodology. While dental disability did not affect the majority (75%) of those workers interviewed, 25% reported an episode of work loss in the past 12 months related to dental problems and dental treatment visits. Workers lost an average of 1.7 hours. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
24

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 2 publications
1
39
0
24
Order By: Relevance
“…Several studies have shown perception of need as the characteristic with highest explanation power for the search for dental assistance. Dental pain is not always enough to motivate a visit to the dental service 29 . From workers reporting toothache in the last six months and not having looked for oral health services, 46.9% have not perceived the need and 12.0% failed to do it due to lack of money, which may suggest a lack of third shift dental assistance in the public service or not having been waived for treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown perception of need as the characteristic with highest explanation power for the search for dental assistance. Dental pain is not always enough to motivate a visit to the dental service 29 . From workers reporting toothache in the last six months and not having looked for oral health services, 46.9% have not perceived the need and 12.0% failed to do it due to lack of money, which may suggest a lack of third shift dental assistance in the public service or not having been waived for treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Na Dinamarca, em 1975, os pacientes que fizeram uso regular dos serviços odontológicos (uma vez por ano nos últimos cinco anos) receberam tratamento que conservaram a estrutura dental, enquanto aqueles que foram ao cirurgião-dentista no mesmo período, irregularmente ou há mais de cinco anos, receberam tratamentos mais radicais como exodontias e pró-teses 13 . Além disso, indivíduos que realizaram visitas preventivas foram menos propensos a se ausentar do trabalho e tiveram menor número de horas de trabalho perdidas 14 .…”
Section: Introductionunclassified
“…Further, these benefits are easy to overlook due to the difficulties of quantifying them in economic terms. In particular, it is unclear how these benefits may offset lost worker productivity [19][20][21][22][23][24] . If it were possible to calculate all ANOVA such factors as benefits, the benefit-cost ratio would be larger than indicated in this paper.…”
Section: Anovamentioning
confidence: 99%